Interferon gamma-induced apoptosis of head and neck squamous cell carcinoma is connected to indoleamine-2, 3-dioxygenase via mitochondrial and ER stress-associated pathways. Issue 1 (March 2016) - El Jamal, Siraj; Taylor, Erin; Abd Elmageed, Zakaria; Alamodi, Abdulhadi; Selimovic, Denis; Alkhateeb, Abdulaziz; Hannig, Matthias; Hassan, Sofie; Santourlidis, Simeon; Friedlander, Paul; Haikel, Youssef; Vijaykumar, Srinivasan; et al.
Abstract Background Tumor response to immunotherapy is the consequence of a concerted crosstalk between cytokines and effector cells. Interferon gamma (IFNγ) is one of the common cytokines coordinating tumor immune response and the associated biological consequences. Although the role of IFNγ in the modulation of tumor immunity has been widely documented, the mechanisms regulating IFNγ-induced cell death, during the course of immune therapy, is not described in detail. Results IFNγ triggered apoptosis of CLS-354 and RPMI 2650 cells, enhanced the protein expression and activation of indoleamine 2, 3-dioxygenase (IDO), and suppressed the basal expression of heme oxygenase-1(HO-1). Interestingly, IFNγ induced the loss of mitochondrial membrane potential (Δψ m) and increased accumulation of reactive oxygen species (ROS). The cytokine also induced the activation of Janus kinase (JAK)/Signal Transducer and Activator of Transcription (STAT)1, apoptosis signal-regulating kinase 1 (ASK1), p38, c-jun-N-terminal kinase (JNK) and NF-κB pathways and the transcription factors STAT1, interferon regulatory factor 1 (IRF1), AP-1, ATF-2, NF-κB and p53, and expression of Noxa protein. Furthermore, IFNγ was found to trigger endoplasmic reticulum (ER) stress as evidenced by the cleavage of caspase-4 and activation of protein kinase RNA-like endoplasmic reticulum kinase (PERK) and inositol-requiring-1α (IRE1α) pathways. Using specific inhibitors, we identified a potential role for IDO as apoptotic mediator in the regulation of IFNγ-induced apoptosis of head and neck squamous cell carcinoma (HNSCC) cells via Noxa-mediated mitochondrial dysregulation and ER stress. Conclusion In addition to the elucidation of the role of IDO in the modulation of apoptosis, our study provides new insights into the molecular mechanisms of IFNγ-induced apoptosis of HNSCC cells during the course of immune therapy.